A long way to the State: actors and temporalities of the nationalization of Argentine television (1934-1974) (Quinto Sol, 2022)
The research reconstructs the process of nationalization [read statization] of television in Argentina. For this, three major aspects are analyzed: the overlapping of the concepts of State and nation associated with radio and television, the role of the Doctrine of the Internal Enemy in the official broadcasting policy and the debates around statization at the time of its implementation. These are, respectively, the main lines of the long, medium and short term of the process.The sources of information were mainly newspapers, magazines, official documents and legislation. In them we identify and reconstruct the positions and links between the military, politicians, businessmen and union members regarding the issue.The work offers two fresh approaches that distinguish it from the existing literature. On the one hand, it moves away from a viewpoint exclusively focused on television, to reintegrate the problem from an overall view of radio and television, to preserve the intelligibility of State policy, which was only one for both media. On the other hand, we propose to break with a periodization that identifies the roots of the process with the beginning of the third Peronism. Both perspectives follow the objective of understanding longer-term dynamics that run throughout dictatorship and democracy in the History of the media in Argentina.
Keywords: television broadcasting policy nationalization Armed Forces businessmen; television; broadcasting policy; nationalization; Armed Forces; businessmen